The Regularity and Irregularity of Travel: an Analysis of the Consistency of Travel Times Associated with Subsistence, Maintenance and Discretionary Activities - Thomas Longden (Fondazione Eni Enrico Mattei (FEEM), 2016)
Regular and irregular travel patterns coincide with different underlying purposes of travel and days of the week. Within this paper, it is shown that the balance between subsistence (i.e. work) and discretionary (i.e. leisure) activities is related to differences in travel patterns and explains consistency across years. Using eight years of time use diary entries this paper finds that travel time related to subsistence activities tends to be regular and stable. In contrast, travel time associated with discretionary activities tends to be more unpredictable and varies greatly between discretionary and non-discretionary days. These findings have consequences for the travel time budget literature as consistency of average travel time is found to be driven by work days, which are frequent and have stable travel times. This is offset by discretionary days as they tend to have longer travel times with greater variability but are fewer in number.
Keywords: R4; R41; 330; Travel Time Stability; Time Allocation; Discretionary Activities; Switching Model